До історії вилучення радянською владою цінностей із дорогоцінних металів на Чернігівщині (1921 р.) - Блакитний, М.М. (Сiверянський літопис, 2021)
Мета статті – висвітлення грабіжницької політики державного терору радянської влади щодо примусового вилучення цінностей із дорогоцінних металів у цивільного населення, церковних громад та монастирів на Чернігівщині в 1921 р. На початку 20-х рр. ХХ ст. керівництво радянської Росії бере злочинний курс на масову конфіскацію виробів із дорогоцінних металів, коштовного каміння. Це була масштабна кампанія з вилучення цінного майна в населення, а в її рамках проводили конфіскацію цінностей у Церкви, що супроводжували антирелігійною пропагандою. Якщо в 1918–1920 рр. більшовики проводили конфіскації під час військових дій, то в 1921–1922 рр. масовий грабунок населення відбувався в мирний час, але із залученням армії. Безпрецедентна акція з вилучення дорогоцінних металів у цивільного населення, церковних громад та монастирів проходила в кілька етапів. Рішення про початок злочинної кампанії з конфіскації виробів із дорогоцінних металів приймав уряд РСФРР – Рада народних комісарів, а впроваджували чиновники-маріонетки радянської України. Кампанія з вилучення цінностей проходила у 12 повітах Чернігівської губернії. Наукова новизна публікації полягає в тому, що вперше були оприлюднені окремі документи з Державного архіву Чернігівської області, які висвітлюють особливості першого етапу вилучення дорогоцінного майна в населення і монастирів на Чернігівщині. Пропоновані документи розкривають окремі епізоди примусового вилучення цінностей у цивільного населення Чернігова, початок грабунку церков і монастирів (на прикладі конфіскації срібної раки св. Феодосія з Борисоглібського собору Чернігова й майна Максаківського монастиря в Сосницькому повіті), спроби порятунку культурних цінностей Максаківського монастиря науковцями та музейниками В. Шугаєвським і Б. Пилипенком. Рішення про вилучення й конфіскацію приймала колегія Чернігівської губернської надзвичайної комісії. Речі передавали в Чернігів до губернського фінвідділу. Надалі, світське й культове срібло відправляли в ГОХРАН (Москва). У цивільного населення вилучали прикраси, побутові речі, гроші, а в церквах і монастирях – шедеври українського золотарства, духовні святині, срібні оклади ікон, предмети культу. Висновки. Початок проведення конфіскацій по церквах і монастирях виробів з дорогоцінних металів стало прологом великої антицерковної кампанії 1922 р., яку супроводжував масовий грабунок церков Чернігівської губернії. Унаслідок примусового вилучення коштовного майна в 1921 р. Чернігівщина й український народ втратили велику кількість матеріальних цінностей, культурно-мистецьких, духовних творів та святинь. The purpose of the article is to characterize the predatory policy of state terror of Soviet Russia regarding the forcible confiscation of valuables from precious metals from the civilian population, church communities and monasteries in the Chernihiv region in 1921. In the early 1920s the leadership of Soviet Russia had taken a criminal course on the mass confiscation of articles made from precious metals and precious stones. It was a large-scale campaign to confiscate valuable property from the population, and it included the confiscation of valuable possession from the church, which was accompanied by anti-religious propaganda. If in 1918–1920 the Bolsheviks carried out confiscations during hostilities, in 1921–1922 the mass plunder of the population took place in peacetime, but with the involvement of the army. The unprecedented action of extracting precious metals from the civilian population, church communities and monasteries took place in several stages. The decision to start a villain campaign to confiscate precious metal products was made by the government of Soviet Russia, the Council of People's Commissars, and implemented by puppet officials of Soviet Ukraine. The campaign to seize valuables took place in 12 counties of Chernihiv province. The scientific novelty is that for the first time some documents from the State Archive of Chernihiv region were published, which cover the features of the first stage of confiscation of valuable property from the population and monasteries in Chernihiv region. The proposed documents reveal some episodes of forced confiscation of valuables from the civilian population of Chernihiv, the beginning of the looting of churches and monasteries (for example, the confiscation of the silver crab of St. Theodosius from Borisoglebsk Cathedral of Chernihiv and the property of Maksakivsky Monastery in Sosnytsia county). Also, there were attempts to save cultural valuables by researches and the museum employees V. Shugaevsky and B. Pilipenko. The decision on seizure and confiscation was made by the board of the Chernihiv Provincial Extraordinary Commission. Things were transferred to the provincial financial department in Chernihiv. Later, secular and cult silver was sent to GOHRAN (State Treasure of the Russian Socialist Federal Soviet Republic, Moscow). Jewelry, household items, and banknotes were confiscated from the civilian population and masterpieces of Ukrainian goldsmiths, spiritual shrines, silver icons, cult objects – from churches and monasteries. Conclusions. The beginning of confiscations of precious metal products in churches and monasteries was the prologue to the great anti-church campaign of 1922, which was accompanied by a mass looting of churches in the Chernihiv province. As a result of the forcible seizure of valuable property in 1921, Chernihiv region and the Ukrainian people lost a large number of material values, cultural, artistic, spiritual works and shrines.